EMPOWERMENT OF PKK WOMEN IN MUARO SENTAJO VILLAGE THROUGH ORCHID CULTIVATION COMMERCIALIZATION AND DIGITAL MARKETING TRAINING - Pebra Heriansyah; Seprido Seprido; Helpi Nopriandi; Wiko Susandy Edika Putra; Puti Annisa Ilhasana (PT. Jurnal Center Indonesia Publisher, 2026)
Muaro Sentajo possesses the potential to be developed as a production hub for native orchid species due to its location within the natural habitat of orchid species in Kuantan Singingi Regency, directly bordering the Sentajo Raya protected forest. Furthermore, the village has an underutilized female labor potential, organized within the Family Welfare Movement (Pemberdayaan dan Kesejahteraan Keluarga / PKK) as the foundational collective for rural women in Muaro Sentajo. This initiative aims to provide knowledge on native orchid species, cultivation techniques, integrated systems with stingless bees (kelulut), and digital marketing. The program implemented a Participatory Action Research (PAR) approach, consisting of asset mapping, practical cultivation workshops, e-commerce platform development, and four months of intensive mentoring. This empowerment program successfully established an active orchid breeding group managing more than 15 native orchid species. Additionally, 83.66% of the participants demonstrated proficiency in operating digital marketing channels (Instagram and Shopee), resulting in the first independent commercial sales of local orchid products. The integration of local ecological assets with modern digital marketing proved effective in enhancing the economic independence of rural women and promoting sustainable community development.